2011
DOI: 10.1038/ng.868
|View full text |Cite
|
Sign up to set email alerts
|

De novo nonsense mutations in ASXL1 cause Bohring-Opitz syndrome

Abstract: Bohring-Opitz syndrome is characterized by severe intellectual disability, distinctive facial features and multiple congenital malformations. We sequenced the exomes of three individuals with Bohring-Opitz syndrome and in each identified heterozygous de novo nonsense mutations in ASXL1, which is required for maintenance of both activation and silencing of Hox genes. In total, 7 out of 13 subjects with a Bohring-Opitz phenotype had de novo ASXL1 mutations, suggesting that the syndrome is genetically heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
241
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 13 publications
5
241
0
3
Order By: Relevance
“…33 Recently, we showed that combining data from three individuals was sufficient to identify the gene for Bohring-Opitz syndrome. 34 Although in the individual patients we found between 130 and 222 novel non-synonymous variants, the overlap for any two patients yielded 26 candidate genes whereas the overlap from three patients pointed only to a single gene.…”
Section: Affecting Protein Sequencementioning
confidence: 71%
See 1 more Smart Citation
“…33 Recently, we showed that combining data from three individuals was sufficient to identify the gene for Bohring-Opitz syndrome. 34 Although in the individual patients we found between 130 and 222 novel non-synonymous variants, the overlap for any two patients yielded 26 candidate genes whereas the overlap from three patients pointed only to a single gene.…”
Section: Affecting Protein Sequencementioning
confidence: 71%
“…After this, typically between 150 and 500 private non-synonymous or splicesite variants are prioritized as potential pathogenic variants (see Figures 1 and 2). 4,[28][29][30][31][32][33][34] It is important to emphasize that prioritization may discard the pathogenic variant. A variant that is present at low frequency in a heterozygous state in the normal population may be removed even though it causes disease if present in a homozygous state.…”
Section: Disease Gene Identification Strategies For Exome Sequencingmentioning
confidence: 99%
“…[3][4][5] In 2011, germline mutations in ASXL1 (MIM *612990) were shown to be causative for Bohring-Opitz syndrome. 6 ASXL3 and ASXL1 belong to the same gene family. Together with ASXL2 (MIM *612991), they constitute the ASXL family of additional sex combs like genes, human homologs of the Asx gene in Drosophila, 7 which serve as epigenetic scaffolding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous ASXL1 truncating mutations have been identified as the main cause of BOS 1, 2. A recent publication 3 called the attention to the fact that mutations associated with BOS are also present in the ExAC (Exome Aggregation Consortium) database 4.…”
Section: Introductionmentioning
confidence: 99%